PERGESERAN PARADIGMA PENGENALAN AL-QUR’AN DI INDONESIA - Zahro, Rodliyatuz (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2023)
Various methods of recognizing hijaiyah letters have emerged in Indonesia, both in the form of software, books and circulation on social media. There were 91 guidebooks for the introduction of hijaiyah letters spread across Indonesia, from the first century to the 21st century. This research tries to see the paradigm shift in the introduction of hijaiyah letters circulating in Indonesia from the 1st century to the 21st century, using a sociological approach. The research results show a shift in method paradigms from the first century to the 21st century. This shift can be influenced by three aspects; sociology, ideology, and economics. Only one method emerged in Indonesia in the first period (the beginning of the arrival of Islam until the 19th century), with the sociological condition of Indonesian society which still lacked religious understanding, making this method valid for a long time in Indonesia. Shifting to the second period (20th century) several methods that emerged were influenced by social factors with the emergence of methods that used the analogy of Latin letters. The paradigm shift in methods that emerged from the second period towards the third period appeared to be influenced by economics and ideological groups, the methods that emerged tended to display variants or styles that attracted the attention of the public, and some methods that limited their distribution to certain groups.